IMPROVING SALES ACTIVITY ENTERPRISES BY CREATING DISTRIBUTION CENTER - V. Zhukov (Вестник университета)
We considered and analyzed the reasons for the creation of a centralized distribution centers by large international companies. Showing positive features of this process on the example of Russian and foreign companies.